PSYCHOLOGICAL AND PEDAGOGICAL PRINCIPLES OF CONSTRUCTION STUDENT DIALOGUE WITH COMPUTER - A.S. Chumak (Academy of Cognitive and Natural Sciences, 2008)
In the article the use of computer on the lessons of technology and his influence is on forming of creative capabilities of students.  умовах економічних змін у країні в